In Vitro Antibacterial Activity and Minimum Inhibitory Concentration of Citrus aurantifolia Lime Peel Ethanolic Extract against Propionibacterium acnes - Putri, Amalia Eka; Negara, Sri Bintang Sahara Mahaputra Kusuma (CV. Nusantara Scientific Medical, 2023)
Propionibacterium acnes (syn. Cutibacterium acnes) is the principal gram-positive anaerobe implicated in acne vulgaris through lipolysis, follicular obstruction, and pro-inflammatory cytokine induction. Rising antibiotic resistance among P. acnes strains necessitates plant-derived alternatives. This study evaluated the in vitro antibacterial activity and minimum inhibitory concentration (MIC) of Citrus aurantifolia lime peel ethanolic extract against P. acnes ATCC 6919 using the Kirby-Bauer disc diffusion method on Muller Hinton Agar (MHA). The extract was prepared by maceration with 96% ethanol from lime peels collected in Tulungagung, East Java, Indonesia. Fourteen concentrations (0.5–150 mg/mL) were tested in triplicate. The MIC was established at 1 mg/mL with an inhibition zone of 7.23 ± 0.15 mm. Inhibition zones increased proportionally with concentration, reaching 12.20 ± 0.10 mm at 150 mg/mL. Positive control (tetracycline 30 µg) produced 31.13 ± 0.38 mm. Antibacterial activity is attributed to multi-target mechanisms of flavonoids, tannins, alkaloids, and saponins acting on the cell wall, membrane, DNA, and virulence enzymes of P. acnes. These findings support the development of lime peel extract as a natural anti-acne ingredient.